Discursive (re)productions of (im)possible students in the Canadian prairies. Issue 6 (2nd November 2019) - Gebhard, Amanda
ABSTRACT: This article applies post-structural theories of discourse, power, and performativity to trouble dominant ways of knowing Aboriginal education in the Canadian Prairies that racialize student subjects. A discourse analysis of interview transcripts traces how discourses of innocent teachers and (im)possible Aboriginal learners deploy the historicity of colonial forces to (re)create the conditions of possibility for exclusionary educational practices. The author employs the concept of 'impossible student' to analyse teachers' negotiation of discourses that position Aboriginal students as everything the 'good' student is not, and thus outside the bounds of studenthood – before they even arrive at school. The concept of discursive performatives is used to offer insights into how persistent inequalities in Aboriginal education might be shifted within everyday practices, and to argue the need for rethinking what it means to be a teacher and a learner in a settler society.